A study on conservation of architectural housing units in the context of sociocultural structure and alteration: case of Cappadocia–Güzelyurt/Turkey. (2nd January 2016) - Şahin, Ebru; Aksulu, Behiye Işık
Abstract : In urban life with ever evolving, growing and changing cultural and physical dynamics, traditional urban fabric should be preserved and this conservation should be made sustainable. This urban scale conservation can only be ensured by understanding physical and cultural structure and values of traditional fabric. Only a conservation operation which is prepared in a holistic scope and involves social, physical, functional and aesthetic solutions can enable the determination of place and importance of traditional historical fabric in urban- and regional-scale and revelation of its usability using appropriate methods for appropriate purposes. Traditional housing fabric of Güzelyurt has faced the problem of conservation following sociocultural transformation in the settlement. In this study, this conservation was discussed within the changing social structure, and traditional housing fabric was described, investigated and classified within its cultural context.